Experimental Analysis OF Heat Transfer and Pressure Drop for Tube-in-fin Heat Exchangers Using Ice Slurry in HVAC System - N. Azhaguvel, P. Bharathidasan* (Recent Research in Science and Technology, 2010)
Abstract Ice slurries can be used both for cold storage in place of chilled water or ice and as a secondary refrigerant since, up to certain concentrations, they can be pumped directly through distribution pipe works and heat exchangers. For ice slurries to become more widely accepted, however, more engineering information is required on fluid flow and heat transfer characteristics. This paper reports on the results of experimental investigations of heat transfer and pressure drop of 14 % ice fraction, 16% ethylene glycol, and 70% water by volume flowing in a tube-fin exchanger. And the airflow rate is varied from between 1 m/s to 3 m/s. In this flows range, due the ice fractions caused around a 5% in the pressure drop. The overall heat transfer capacity of the heat exchanger was found to increase by more than 26% with melting ice slurry flow compared to chilled water flow. In a practical application, for a given thermal load this would lead to between 70% and 80% reduction in flow rate and pressure drop compared to chilled water cooling systems. Keywords: Heat transfer, Pressure drop, Ice slurry